Assessment and re-design of learning activities from young social work students' perceptions and experiences: an empirical study on the subject "social work with groups" of the University of Alicante (Spain) - Domenech-López, Yolanda; Giménez-Bertomeu, Víctor M. (Social work education, 2020)
Background. This article aims to incorporate students' visions in the design of learning activities based on an analysis of their perceptions and evaluations of their experience working in small groups carried out in the subject "Social Work with Groups" of a Social Work Program (University of Alicante, Spain). Method. We followed a quantitative approach, using a survey to collect data. Participants were social work students (n = 69). Univariate and bivariate data analysis was carried out, and we used parametric and non-parametric tests, depending on the group sample size. Results. Students believe that the activity contributes to achievement of learning objectives and skill and content acquisition and consolidation. Global satisfaction with the evaluation system and the activity was adequate. We found some differences by group in terms of associations between perception and satisfaction and some sociodemographic and academic variables. Conclusion. The experience was evaluated positively by the students. The activity design puts students at the center of the teaching and learning process.